MP56: Intraosseous versus intravenous access in pediatric out-of-hospital cardiac arrest: an examination of prehospital vascular access methods and survival rates. (May 2020) - Besserer, F.; Dirk, J.; Meckler, G.; Tijssen, J.; DeCaen, A.; Kawano, T.; Grunau, B.
Abstract : Introduction: Intraosseous (IO) and intravenous (IV) access to the vascular system for the delivery of fluid and medication is a component of advanced pediatric resuscitation. Data describing the use of IV or IO vascular access methods and outcomes of pediatric out-of-hospital cardiac arrest (OHCA) are limited. Methods: We analyzed prospectively collected data of non-traumatic OHCA of the Resuscitation Outcomes Consortium registry in Canada and the USA (2011-2015). We included patients 17 years of age and younger who were treated by emergency medical services (EMS). We described the vascular access routes utilized, and the success rate of these attempts. We performed a logistic regression model, to evaluate the association of vascular access route and survival, adjusting for age, sex, shockable initial rhythm, witnessed status, public location, EMS arrival interval and time from 911 call to vascular access. In this model, we excluded patients with failed, multiple site or no vascular access attempts during the resuscitation. Results: Of 1549 non-traumatic pediatric OHCA, 822/895 (92%) and 345/488 (71%) had successful IO and IV vascular access attempts, respectively. IO access was more common in younger cases. Of 761 cases included in the regression model, 30/601 (5%) of IO-treated cases survived to hospital discharge, in comparison to 40/160 (25%) of IV-treated cases. Intraosseous access was associated with a decreased survival to hospital discharge (adjusted OR 0.46; 95% CI 0.21 to 0.98). Conclusion: In pediatric patients with OHCA, intraosseous vascular access was more commonly successful than IV placement and more common among younger cases. However, in cases with successful vascular access, IO use was associated with lower survival to hospital discharge.